2011
DOI: 10.1007/s00709-011-0339-5
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules and the tax payer

Abstract: Plant microtubules have evolved into a versatile tool to link environmental signals into flexible morphogenesis. Cortical microtubules define the axiality of cell expansion by control of cellulose orientation. Plant-specific microtubule structures such as preprophase band and phragmoplast determine symmetry and axiality of cell divisions. In addition, microtubules act as sensors and integrators for stimuli such as mechanic load, gravity, but also osmotic stress, cold and pathogen attack. Many of these function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 112 publications
(107 reference statements)
0
11
0
2
Order By: Relevance
“…33 Interestingly, treatment of A. thaliana leaves with DPI that reduces ROS levels alleviates the effects of V. dahliae toxins on the MT cytoskeleton. In addition, Nick 34 noted that biotic stress perception depends on MTs and is also mediated by RBOHC (respiratory burst oxidase homolog), the plant homolog of the NADPH oxidase that upon activation catalyzes ROS production in the apoplast.…”
Section: Imbalanced Ros Levels and Atypical Tubulin Polymer Formationmentioning
confidence: 99%
“…33 Interestingly, treatment of A. thaliana leaves with DPI that reduces ROS levels alleviates the effects of V. dahliae toxins on the MT cytoskeleton. In addition, Nick 34 noted that biotic stress perception depends on MTs and is also mediated by RBOHC (respiratory burst oxidase homolog), the plant homolog of the NADPH oxidase that upon activation catalyzes ROS production in the apoplast.…”
Section: Imbalanced Ros Levels and Atypical Tubulin Polymer Formationmentioning
confidence: 99%
“…Several authors have suggested that gravitropic bending can trigger altered MT organization (Ikushima and Shimmen, 2005; Jacques et al, 2013; Toyota and Gilroy, 2013). In addition, gravitropism can be inhibited by antimicrotubular drugs or mutations affecting the dynamics of MT (Nick, 2012). On the contrary, tropic bending occurred in roots pretreated with microtubule depolymerizing agents (Bisgrove, 2008).…”
Section: Identification Of Cellular and Molecular Actors In Gravisensmentioning
confidence: 99%
“…). Besides, diverse types of stress induce reorganization of the microtubule (MT) cytoskeleton, thus MTs are nowadays considered as emerging components of plant sensory mechanisms (Nick ).…”
Section: Introductionmentioning
confidence: 99%